2001
DOI: 10.1002/ccd.1184
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of atrial septal defect using Amplatzer septal occluder in Chinese adults

Abstract: Amplatzer septal occluder (AGA Med. Co., USA) is a novel device for occlusion of atrial septal defect. We present our experience of transcatheter closure of atrial septal defects using Amplatzer septal occluder in 45 adult Chinese patients (age range 18-69 years). The size of atrial septal defect varied from 14-28 (23 +/- 4) mm. Cardiac catheterization revealed a pulmonary-to-systemic shunt ratio ranging from 1.4-2.8 (mean 2.0 +/- 0.4). The procedure was successful in 44 (98%) patients. Displacement of the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Thus avoiding subsequent surgical scar and postoperative pain. 4,6,7 The other advantages are less psychological impact, shorter hospital stay, and less need for blood transfusion. 5,7 The absence of myocardial scar may decrease the incidence of incisional dysrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus avoiding subsequent surgical scar and postoperative pain. 4,6,7 The other advantages are less psychological impact, shorter hospital stay, and less need for blood transfusion. 5,7 The absence of myocardial scar may decrease the incidence of incisional dysrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 The other advantages are less psychological impact, shorter hospital stay, and less need for blood transfusion. 5,7 The absence of myocardial scar may decrease the incidence of incisional dysrhythmias. 7 Device implantation success rate of 98.4% is comparable to studies around the world where the success rate of device closure remained between 94-99%.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transesophageal echocardiographic and fluoroscopic confirmation of the device position gives no cue to the security of the device position. We recently experienced a patient who after initial confirmation of the device position was found to have migration of the device at 1 month after the procedure [3]. Therefore, despite apparently successful repositioning of the device by snaring the microscrew, we would recommend elective surgical removal of the device together with simultaneous direct surgical closure of the atrial septal defect during the operation.…”
Section: To the Editormentioning
confidence: 96%
“…As the article from Lee et al [6] and several other registries have demonstrated, this modality is safe and can be applied to a wide variety of ASD patients with significant comorbidites. In the case of PFO, recurrent thromboembolism is low at 5 years and may be negligible after 2 years [1].…”
mentioning
confidence: 93%
“…In this issue, Lee et al [6] report their experience with the Amplatzer septal occluder in a tertiary-care center in Hong Kong. The procedure time was relatively short (67 min on average) and the complication rate was low (2%) in a total of 45 cases.…”
mentioning
confidence: 97%